(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objective: Describe the current status of compliance with outpatient treatment of glaucoma patients at Hanoi Eye Hospital, 2023. Research objective: Direct interviews with 200 glaucoma patients treated as outpatients at Hanoi Eye Hospital. Patients who adhere to treatment are those who comply with all 4 prescribed contents. Research results: Outpatient treatment compliance rate of glaucoma patients was: 31,0%. In which, the compliance rate with the following contents: never forget to apply medicine was 95,5%, regularly apply medicine according to instructions was 40,0%, regularly use medicine on time as prescribed was 59,0% and regularly come for follow-up appointments on time was 60,0%. Conclusion: The compliance rate for outpatient treatment of glaucoma patients was 31,0%, of which the compliance rate for each content ranges from 40,0% to 95,5%.